Interest rate setting and communication at the ECB - Philippine Cour; Alexander Jung (European Central Bank (ECB), 2020)
Based on ordered Probit models and twenty years of euro area data, we estimate empirical reaction functions for the ECB's monetary policy and augment them with communication indicators. First, we find that the ECB responded to risks to price stability in line with its primary objective, and that the account of post-meeting communications about risks to price stability and to growth significantly enhances the modelling of its reaction function. Second, we detect that the ECB also responded to the evolution of the federal funds rate, thereby confirming the importance of international interest rate linkages or the global cycle that it reflects. Third, while confirming Gerlach's (2007) finding on the relevance of M3 growth for explaining future interest rate changes, we show that this result only holds for the period before the global financial crisis.
Keywords: E43; E52; C22; C25; 330; Probit model; monetary policy reaction function; communication indicators; staff projections; Survey of Professional Forecasters